Chromogenic in situ hybridisation (CISH) is a powerful method to detect ALK-positive non-small cell lung carcinomas. Issue 5 (29th November 2013) - Wagner, F; Streubel, A; Roth, A; Stephan-Falkenau, S; Mairinger, T
Abstract : Aim: We assessed the potential of a chromogenic in situ hybridisation (CISH) assay in comparison with quantitative reverse transcription (RT)-PCR (qPCR) to detect anaplastic lymphoma kinase (ALK) break apart-positive lung carcinomas. Methods: Dual-colour CISH using a break apart probe for the ALK gene on 2p23 was performed with 181 formalin-fixed, paraffin-embedded tissue and agar block sections from 175 cases of non-small cell lung carcinomas (NSCLC). Stained slides were analysed with a standard bright-field microscope at 1000× magnification by counting signals from 60 non-overlapping nuclei from three different tumour areas. Samples with ≥15% of positive nuclei were judged as ALK break apart-positive. All samples were simultaneously analysed by qPCR for EML4-ALK to validate CISH results, and positive samples were subject to Sanger sequencing. Results: CISH was successful with 173 of 181 hybridised samples (96%), and seven ALK break apart-positive cases were detected. CISH signals were specific and distinct for both colours. All positive cases were confirmed by qPCR and Sanger sequencing, and concordance between CISH and qPCR was 100%. Nearly all samples (9/10) which failed by qPCR were accessible to CISH analysis. Conclusions: CISH is a very reliable, convenient and inexpensive method to detect ALK-positive NSCLC. CISH success rate is comparably high as with qPCR, and it detects all ALK break apart events in a single assay. It is of special value when RNA quality is poor, or when small biopsies with a very limited amount of tumour cells have to be analysed.